Conversion of scrap copper into chemical compounds - Climaco, Julia F. (s.n.], 1970)
The purpose of the study is to determine the feasibility of converting scrap copper into copper (II) compounds in order to help relieve the difficulties faced by most science and chemistry classes in rural schools and colleges due to the shortage of copper compounds. The study presents the methods for the preparation of copper (II) compounds from scrap copper and the resulting expenses incurred in such preparation. The research aims to provide stimulus to arouse the sensitivity of science and chemistry teachers to exploit the possibilities of improvising and utilizing substitutes for the more costly imported chemical out of scraps and waste materials from the households, metal workshops, school shops and junk piles.